2007
DOI: 10.1099/jmm.0.46525-0
|View full text |Cite
|
Sign up to set email alerts
|

Saccharomyces cerevisiae strain 905 reduces the translocation of Salmonella enterica serotype Typhimurium and stimulates the immune system in gnotobiotic and conventional mice

Abstract: Previous results in the laboratory of the authors showed that Saccharomyces cerevisiae strain 905, isolated during 'cachaç a' production, was able to colonize and survive in the gastrointestinal tract of germ-free and conventional mice, and to protect these animals against oral challenge with Salmonella enterica serotype Typhimurium or Clostridium difficile. In the present work, the effects of S. cerevisiae 905 on the translocation of Salm. Typhimurium (mesenteric lymph nodes, Peyer's patches, spleen, liver) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 42 publications
4
35
0
6
Order By: Relevance
“…Other Saccharomyces spp. or members of other yeast genera may have probiotic activity similar to that of S. boulardii or even better, as already demonstrated by Martins et al (14,15) in mice models. The objective of this work was to determine whether higher trehalose levels or the capacity to produce large amounts of this sugar were advantageous to microbial survival in in vitro experiments simulating different stress conditions commonly present in the bile salts.…”
Section: Resultssupporting
confidence: 52%
“…Other Saccharomyces spp. or members of other yeast genera may have probiotic activity similar to that of S. boulardii or even better, as already demonstrated by Martins et al (14,15) in mice models. The objective of this work was to determine whether higher trehalose levels or the capacity to produce large amounts of this sugar were advantageous to microbial survival in in vitro experiments simulating different stress conditions commonly present in the bile salts.…”
Section: Resultssupporting
confidence: 52%
“…Treated mice also had a lower mortality rate than naïve controls challenged with S. Typhimurium (Martins et al 2005;Martins et al 2011). S. cerevisiae UFMG A-905 have shown adhesion to some enteropathogenic bacteria, such as E. coli, S. Typhi, and S. Typhimurium (Tiago et al 2012), neutralizing the translocation of the latter from the GIT to the liver, spleen, and mesenteric lymph nodes (Martins et al 2007). This probiotic yeast increased the production of IL-10 and sIgA in healthy mice (Martins et al 2007;Generoso et al 2010).…”
Section: Mechanisms Of Action Of Probiotic S Cerevisiae Strainsmentioning
confidence: 98%
“…S. cerevisiae UFMG A-905 have shown adhesion to some enteropathogenic bacteria, such as E. coli, S. Typhi, and S. Typhimurium (Tiago et al 2012), neutralizing the translocation of the latter from the GIT to the liver, spleen, and mesenteric lymph nodes (Martins et al 2007). This probiotic yeast increased the production of IL-10 and sIgA in healthy mice (Martins et al 2007;Generoso et al 2010). In a mouse typhoid fever model, S. cerevisiae UFMG A-905 reduced both inflammation and IL-6, TNF-α, IFN-γ, and IL-10 levels, due to modulation of signaling pathways responsible for the expression of many inflammatory cytokines, such as NF-κB, AP-1, and MAPK pathways (Martins et al 2011).…”
Section: Mechanisms Of Action Of Probiotic S Cerevisiae Strainsmentioning
confidence: 98%
“…We demonstrated previously that Saccharomyces cerevisiae strain UFMG 905 has potential as a probiotic due to its ability to protect mice against Salmonella enterica serovar Typhimurium and Clostridium difficile infection in a murine model (Martins et al, 2005), and to inhibit bacterial translocation and modulate both local and systemic immunity of mice (Martins et al, 2007;Generoso et al, 2010). Recent immunological data demonstrated that both Saccharomyces boulardii and Saccharomyces cerevisiae UFMG 905 decreased the levels of pro-inflammatory cytokines and modulated the activation of mitogenactivated protein kinases (p38 and JNK, but not ERK1/2), NF-kB and AP-1 signalling pathways, which are involved in the transcriptional activation of pro-inflammatory mediators induced by Salmonella infection (Martins et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%